2014
DOI: 10.1007/s00383-014-3594-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of gastroesophageal reflux disease in congenital diaphragmatic hernia: a multicenter study

Abstract: Diaphragmatic defect of more than 75% was risk factor of future need for antireflux surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Various factors may be associated with poor growth during infancy, including the fact that patients with CDH are sometimes intolerant to EN due to cardiorespiratory instability, deep sedation, or restrictions in volume loading. GER, oral aversion, and allergies can also contribute to difficulties in enteral feeding [14,15]. We previously reported that EN and supportive PN in the acute phase were essential for weight gain during infancy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Various factors may be associated with poor growth during infancy, including the fact that patients with CDH are sometimes intolerant to EN due to cardiorespiratory instability, deep sedation, or restrictions in volume loading. GER, oral aversion, and allergies can also contribute to difficulties in enteral feeding [14,15]. We previously reported that EN and supportive PN in the acute phase were essential for weight gain during infancy [16].…”
Section: Discussionmentioning
confidence: 99%
“…The CDH patients, however, are sometimes intolerant to EN due to cardiorespiratory instability, deep sedation, or restrictions in volume loading. Gastroesophageal reflux and allergies can also contribute to difficulties in enteral feeding . Therefore, the amount of EN received is often affected by the severity of CDH.…”
mentioning
confidence: 99%
“…Gastroesophageal reflux and allergies can also contribute to difficulties in enteral feeding. 7,8 Therefore, the amount of EN received is often affected by the severity of CDH. Controversy also surrounds the appropriate timing and dose of supportive parenteral nutrition (PN) in the acute phase.…”
mentioning
confidence: 99%
“…Identified risk factors include antenatal diagnosis, intrathoracic liver position, patch closure, stomach position, esophageal dysmotility, and tube feeding at discharge. [98][99][100] Gastrointestinal symptoms (GERD, FTT, and OA) are associated with a longer hospital course, prolonged mechanical ventilation, and a longer need for parenteral nutrition. 101 The diagnostic approach for suspected GERD in infants with CDH should be based on standard guidelines.…”
Section: Literature Review Pulmonary Function a Literature Overview mentioning
confidence: 99%